Analisis Kemampuan Pemecahan Masalah pada Soal Cerita Aljabar Ditinjau dari Kepercayaan Diri Siswa SMP. - Nadiah Thifal; Mulia Putra; Nur Azizah (Griya Journal of Mathematics Education and Application, 2026)
Abstract Mathematical problem-solving skills are essential for junior high school students, especially in solving algebra story problems that require contextual understanding, problem modeling, and logical reasoning. This study aims to analyze the impact of self-confidence on junior high school students' ability to solve algebra story problems. This research uses a qualitative descriptive approach with three seventh-grade students from SMP Negeri 25 Kota Bekasi, selected based on their self-confidence levels: high, medium, and low. Data were collected through a self-confidence questionnaire, algebra story problem tests, and semi-structured interviews. Data analysis was done using source triangulation. The results show that students with high self-confidence are more consistent in understanding and solving problems, while students with low self-confidence struggle at the initial stage of problem understanding. These findings highlight the important role of self-confidence in mathematical problem-solving. The study provides new insights into the relationship between self-confidence and error patterns in solving algebra story problems. Keywords: Problem Solving; Story Problems; Algebra Material for Junior High School Abstrak Kemampuan memecahkan masalah matematis sangat penting bagi siswa SMP, terutama dalam soal cerita aljabar yang memerlukan pemahaman konteks, pemodelan masalah, dan penalaran logis. Penelitian ini bertujuan menganalisis pengaruh kepercayaan diri terhadap kemampuan siswa SMP dalam menyelesaikan soal cerita aljabar. Pendekatan yang digunakan adalah deskriptif kualitatif dengan subjek tiga siswa kelas VII SMP Negeri 25 Kota Bekasi, yang dipilih berdasarkan tingkat kepercayaan diri: tinggi, sedang, dan rendah. Data dikumpulkan melalui angket kepercayaan diri, tes soal cerita aljabar, dan wawancara semi terstruktur. Analisis data dilakukan dengan triangulasi sumber. Hasil penelitian menunjukkan bahwa siswa dengan kepercayaan diri tinggi lebih konsisten dalam memahami dan memecahkan masalah, sementara siswa dengan kepercayaan diri rendah kesulitan pada tahap awal pemahaman masalah. Temuan ini menunjukkan bahwa kepercayaan diri berperan penting dalam pemecahan masalah matematis. Penelitian ini memberikan wawasan baru tentang hubungan kepercayaan diri dengan pola kesalahan dalam pemecahan soal cerita aljabar. Kata Kunci: Pemecahan Masalah; Soal Cerita; Materi Aljabar SMP